Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai Puskesmas Pangkalan Kabupaten Karawang - Hoeruddin; Suroso; Karnama, Maman Mulya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to analyze the effects of work motivation on the staff at Base Puskesmas, both individually and in conjunction with work discipline. This investigation made heavy use of quantitative techniques. Sixty people from the Base Health Center took part in the study. Saturated slingapple sampling was used in this study. In this research, linear regression analysis was performed at a significance level of 5% using the f test and t test. The study found that pegawwai employees' performance improved when they were more disciplined at work (tvalue = 2,623) > ttable = 2,002, and that Base Health Center employees' performance improved when they were more motivated at work (fvalue = 26,095) > ftable = 3,158. Motivation and workplace discipline only accounted for 47.8% of the variance in performance because other factors accounted for the remaining 52.2%. Keywords: Work motivation, Work discipline, Employee Performance.